Intramedullary/intraosseous myelolipoma in a patient with pathologic fracture - Anoshia Afzal; Sepideh N. Asadbeigi; Maria Kamal; Lewis Hassell; Kar-Ming Fung (BMC, 2022)
Abstract Background Intramedullary lipomatous tumors are rare and mostly reported in the metaphysis of the femur, tibia, and fibula. Myelolipomas are very rare tumors composed of adipose tissue and hematopoietic cells commonly reported in adrenal gland. We report the first reported case of intraosseous myelolipoma with a pathologic fracture in a young woman. Case presentation Patient is a young woman who carried a diagnosis of systemic lupus erythematosus, antiphospholipid syndrome, and hyperparathyroidism. Radiologic studies were done after the patient reported right lower leg pain lasting for a month. Radiologic examination showed a large osteolytic lesions with pathologic fracture affecting the medial aspect of the proximal tibia with extensive soft tissue calcification. The initial clinical and radiographic suspicion was brown tumor secondary to the hyperparathyroidism. Curettage of the lesion yielded large fragments of mature adipose tissue punctuated by a variable amount of mature hematopoietic cells. The histopathologic features were suggestive of myelolipoma. The overall radiographic and histopathologic features supported a diagnosis of myelolipoma. The diagnosis of intraosseous myelolipoma can be challenging in small samples such as core biopsies. Conclusions The differential diagnoses of intraosseous myelolipoma include normal bone marrow, intramedullary hematopoiesis, and other benign lesions. The gold standard diagnosis is histopathologic examination. However, clinical and radiographic features have important roles in the diagnosis of this rare lesion. Due to the rarity of this tumor and lack of formal guidelines for management, the case-to-case basis treatment is recommended.